ANALISIS REAKSI PASAR MODAL TERHADAP PERISTIWA PERANG RUSIA DAN UKRAINA (Studi Kasus Perusahaan Mineral yang Terdaftar Pada ISSI) - Muhammad Izzuddin Al Fathi (2023)
The conflict between Russia and Ukraine has significant implications for the global economy due to indications of rising prices of various commodities such as gasoline and coal. The purpose of this study is to determine the difference in the ratio of abnormal return, return security variability, and trading volume activity before and after the Russian invasion of Ukraine on the ISSI index. Event study is the research methodology used. Wilcoxon signed rank and paired sample t-test with an observation period of 15 days were used as analysis techniques in this study. The data showed that the abnormal rate of return and variability return of the securities were the same before and after the Russian invasion of Ukraine, but there were changes in trading volume between the two times